The Impact of Audiovisual Learning Media to Religiousity of The Student in Islamic History Class - Hakim, Zun Azizul; Hamzah, Muhammad Farid (Nusantara Journal of Behavioral and Social Science, 2022)
The teacher has to make sure that the student in their class, not only improve their knowledge but also improve their attitude. Religiosity is a psychological aspect that must be improved after a student joins an Islamic class. One of the subjects related to Islamic teaching is history class. Audiovisual media is one of the media that the teacher must use in the modern era. By using audiovisual media students will be stimulated to make an imagination related to the subject they learned. The imagination hopefully can touch their heart more, so it can impact to religiosity. The aim of this research is to know how audiovisual learning media on history class can impact student religiosity of the students. Untreated control group design only post-test was used as the research design. Two classes from an Islamic elementary school participate in this research, one as the experiment group and the other as a control group. The participant took from Tulungagung district. To analyze the data, a t-test was used. From the data analysis, it can be inferred that there is significant increment of the religiosity caused by audiovisual learning media that used by the teacher t(41)=2,861, P=0,001 (p less than 0,05).